The The Use of Busuu for Learning Listening in English - Meniwati Meniwati; Ira Mutiaraningrum (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
M-learning has gained remarkable popularity in language learning. Mobile-assisted language learning offers learning opportunities outside the classroom. This study is a smaller part of a bigger project. This study has strived to highlight the advantages of the use of a mobile-assisted language learning application named Busuu in supporting students’ listening practice. Participants involved in this study were 32 first-year college students who have used Busuu for two months. Students used Busuu for listening practice and regularly report their progress to the lecturers. The study revealed that Busuu widens vocabulary range, provides listening practices, has attractive and interactive features, and fosters learning autonomy. Students also wrote that the use of mobile applications is very useful, due to their practicality, portability, flexibility, and accessibility. In addition, it opens up learning opportunities and immediate feedback for learning. Thus, Busuu is promising to be used in listening classroom.